2015
DOI: 10.1155/2015/385395
|View full text |Cite
|
Sign up to set email alerts
|

Delta Cell Hyperplasia in Adult Goto-Kakizaki (GK/MolTac) Diabetic Rats

Abstract: Reduced beta cell mass in pancreatic islets (PI) of Goto-Kakizaki (GK) rats is frequently observed in this diabetic model, but knowledge on delta cells is scarce. Aiming to compare delta cell physiology/pathology of GK to Wistar rats, we found that delta cell number increased over time as did somatostatin mRNA and delta cells distribution in PI is different in GK rats. Subtle changes in 6-week-old GK rats were found. With maturation and aging of GK rats, disturbed cytoarchitecture occurred with irregular beta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
4
14
0
1
Order By: Relevance
“…The number of δ‐cells was increased in early stages of the syndrome and the elevated volume density coincided with massive β‐cell necrosis . Additionally, in diabetes, a local overproduction of somatostatin could diminish β‐cell viability and might contribute to the deterioration of β‐cell mass through paracrine effects as speculated by Alán et al . who found a hyperplasia of δ‐cells in pancreatic islets of GK rats.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The number of δ‐cells was increased in early stages of the syndrome and the elevated volume density coincided with massive β‐cell necrosis . Additionally, in diabetes, a local overproduction of somatostatin could diminish β‐cell viability and might contribute to the deterioration of β‐cell mass through paracrine effects as speculated by Alán et al . who found a hyperplasia of δ‐cells in pancreatic islets of GK rats.…”
Section: Discussionmentioning
confidence: 85%
“…Many studies have focused on the influence of insulin and glucagon in the pathophysiology of diabetes. Diabetes is characterized by both, peripheral insulin resistance and/or pancreatic β‐cell dysfunction as well as hyperglucagonemia . Nevertheless, an impact of somatostatin in the pathogenesis of the disease also has to be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…U naših ekspreimentalnih životinja je konstatovana i hiperplazija D ćelija koje sekretuju somatostatin. Hiperplazija somatostatinskih ćelija je opisana u dijabetesu tip 2 kod ljudi i pacova 27 .…”
Section: Diskusijaunclassified
“…Somatostatin is a peptide hormone released by the delta cells of the pancreas that suppresses the release of insulin and several counterregulatory hormones, including glucagon, catecholamines, growth hormone and cortisol [19]. In humans and in animal models, diabetes causes somatostatin levels to rise systemically [20,21] and within the islets themselves [20,[22][23][24]. By antagonising somatostatin receptor (SSTR)2 with a selective SSTR2 antagonist (SSTR2a), PRL-2903, we have demonstrated that glucagon and corticosterone responses to insulin-induced hypoglycaemia are improved [25,26], as is the depth and duration of hypoglycaemia [27].…”
Section: Introductionmentioning
confidence: 99%